(untitled) (Baghdad Science Journal, 2025)
This study has evaluated the humoral immune response in Golden Hamsters experimentally infected with Leishmania donovani along (4) times of follow up (15, 30, 60, 90) days after infection. Indirect haemagglutination test was used to determine the antibody titer through the various stages of the study. Also the progress of the infection was studied depending on some of the visceral changes caused by the parasite, like weight of liver, length & weight of spleen & the count of Leishmania parasites in spleen were measured. Results has shown that there was an increase in antibody titer & the maximum value was recorded at the 4th day of follow up (90 days after infection) as well as that there was an increase in the length of the spleen, weight of liver & spleen comparing with the control animals, also the count of the parasites in the spleen was increasing gradually through the 4 times of follow up.